1990
DOI: 10.1016/s0010-9452(13)80078-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Remission of Left Hemianesthesia after Vestibular Stimulation. A Sensory Neglect Phenomenon

Abstract: In three right-brain damaged patients with contralesional neglect vestibular stimulation induced a temporary remission of left hemianesthesia, in addition to the well-known transient recovery of extrapersonal and personal neglect. These findings indicate that in neglect patients attentional factors may play an important role in producing apparently "primary" sensory deficits, which may be interpreted in terms of defective access to conscious processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 14 publications
5
87
2
Order By: Relevance
“…The differences between pre-and posttraining responses started at 300 -600 msec after picture presentation and continued for 200 -700 msec. Focal brain lesion studies have suggested that lesions in the left inferior parietal lobe lead to disturbances in spatial tasks (Mattingley, Husain, Rorden, Kennard, & Driver, 1998;Vallar, Sterzi, Bottini, Cappa, & Rusconi, 1990), in acquisition and retrieval of information from episodic memory (Shallice & Vallar, 1990;Shallice & Warrington, 1980), and in the phonological storage component of short-term memory ( Vallar, Di Betta, & Silveri, 1997). Aphasiological studies have indicated that left inferior parietal lesions quite often lead to conduction aphasia, in which phonological output problems are remarkable, or to anomic aphasia (cf.…”
Section: Training-specific Changes In Brain Responsesmentioning
confidence: 99%
“…The differences between pre-and posttraining responses started at 300 -600 msec after picture presentation and continued for 200 -700 msec. Focal brain lesion studies have suggested that lesions in the left inferior parietal lobe lead to disturbances in spatial tasks (Mattingley, Husain, Rorden, Kennard, & Driver, 1998;Vallar, Sterzi, Bottini, Cappa, & Rusconi, 1990), in acquisition and retrieval of information from episodic memory (Shallice & Vallar, 1990;Shallice & Warrington, 1980), and in the phonological storage component of short-term memory ( Vallar, Di Betta, & Silveri, 1997). Aphasiological studies have indicated that left inferior parietal lesions quite often lead to conduction aphasia, in which phonological output problems are remarkable, or to anomic aphasia (cf.…”
Section: Training-specific Changes In Brain Responsesmentioning
confidence: 99%
“…A number of studies have investigated this possibility. Rehabilitation with vestibular stimulation (Cappa, Sterzi, Vallar, & Bisiach, 1987;Vallar, Sterzi, Bottini, Cappa, & Rusconi, 1990), or with optokinetic nistagmus (Pizzamiglio, Frasca, Guariglia, Incoccia, & Antonucci, 1990), both of which produce a re¯ex-ive eye deviation toward the neglected side, yield a reduction of neglect. However, this bene®t is short-lived.…”
Section: Overt and Covert Orientingmentioning
confidence: 99%
“…In light of these figures, it is perhaps not surprising that, over the last 50 years, an increasing number of cognitive rehabilitation techniques have been developed to improve the recovery of neglect patients (for a recent review see Kerkhoff & Schenk, 2012), such as visual scanning training (e.g., Antonucci et al, 1995;Kerkhoff, 1998;Lawson, 1962;Piccardi, Nico, Bureca, Matano, & Guariglia, 2006;Pizzamiglio et al, 1992), limb activation training (e.g., Brunila, Lincoln, Lindell, Tenovuo, & Hamalainen, 2002;, 1994Robertson, Hogg, & McMillan, 1998a;Robertson, McMillan, MacLeod, Edgeworth, & Brock, 2002;Robertson, North, & Geggie, 1992;Samuel et al, 2000), sustained attention training (e.g., Robertson, Tegnér, Tham, Lo, & Nimmo-Smith, 1995;Robertson, Mattingley, Rorden, & Driver, 1998b;Thimm, Fink, Küst, Karbe, & Sturm, 2006), prism adaptation (e.g., Frassinetti, Angeli, Meneghello, Avanzi, & Ladavas, 2002; Jacquin-Courtois, Rode, Pisella, Boisson, & Rossetti, 2008;Rossetti et al, 1998;Vaes et al, 2016; for a recent review see Newport & Schenk, 2012), neck muscle vibration (e.g., Karnath, 1994;Karnath, Christ, & Hartje, 1993;Schindler & Kerkhoff, 2004;Schindler, Kerkhoff, Karnath, Keller, & Goldenberg, 2002), caloric (e.g., Cappa, Sterzi, Vallar, & Bisiach, 1987;Rubens, 1985;Vallar, Sterzi, Bottini, Cappa, & Rusconi, 1990) and optokinetic stimulation (e.g., Bisiach, Pizzamiglio, Nico, & Antonucci, 1996;Karnath, 1996;Kerkhoff, Schindler, Keller, & Marquardt, 1999…”
Section: Introductionmentioning
confidence: 99%